The Effect of Team Word-Webbing Toward Students’ Reading Comprehension at Tenth Grade of MAN Koto Baru, Dharmasraya - Ria Satriani; Melyann Melani; Reflinda Reflinda; Syahrul Syahrul (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study investigates the effect of the Team Word-Webbing technique on reading comprehension among tenth-grade students at MAN Koto Baru, Dharmasraya. Reading comprehension is critical for language acquisition and academic success, as it encompasses the ability to extract and interpret meaning from text. Despite its importance, many students struggle with reading comprehension due to various factors including limited vocabulary and insufficient engagement. To address these issues, the study employed a quantitative experimental design, using a quasi-experimental approach with an experimental group and a control group. The research involved a pre-test and post-test assessment to measure reading comprehension levels before and after the implementation of the Team Word-Webbing technique. The experimental group was taught using this technique, which involves organizing ideas visually to enhance understanding, while the control group received traditional instruction. The sample consisted of two classes selected through purposive sampling, with data analyzed using t-tests to compare outcomes. Results indicated that the Team Word-Webbing technique significantly improved reading comprehension compared to conventional methods. The experimental group demonstrated higher post-test scores, with statistical analysis revealing a significant difference (p < 0.05). This suggests that Team Word-Webbing enhances students' ability to understand and retain reading material by facilitating better organization of ideas and active engagement. In conclusion, the study supports the effectiveness of Team Word-Webbing as an instructional strategy to improve reading comprehension. This technique not only aids in comprehension but also promotes active learning and student interaction, making it a valuable tool for educators aiming to enhance reading skills in the classroom.